PENGARUH SISTEM MODERNISASI ADMINISTRASI PERPAJAKAN, PELAYANAN FISKUS DAN PENGGUNAAN E-SPT TERHADAP KEPATUHAN PAJAK - Ira Prananti, Ni Putu; Rasmini, Ni Ketut (E-Jurnal Akuntansi, 2014)
The purpose of this study was to determine the effect of the tax administration system, the service tax authorities and the use of e-SPT on taxpayer compliance. This research was conducted at the Tax Office Primary Gianyar. The number of samples taken 118 registered Taxpayer and using e-SPT in their tax reporting. Determination Technique selected samples using incidental sampling method. Data collected through interviews, documentation and questionnaires. The analysis technique used is multiple linear regression. Based on the results of the analysis found that the modernization of the tax administration system, the service tax authorities and the use of e-SPT positive effect on the level of taxpayer compliance.
Keywords: modernization tax administration, services, e-SPT